Case Report: Rare Pulmonary Sclerosing Pneumocytoma: Large, Multiple, Metastatic, and Fatal - Zhang, Weidong; Liu, Yuanyuan; Chai, Yamei; Shi, Kefeng; Chen, Jialing; Shi, Dongfeng; Wu, Xiaoming (Frontiers in Medicine, 2021)
Pulmonary sclerosing pneumocytoma (PSP) is a rare benign or low-grade malignant tumor, but it has the potential to present with multiple lesions, lymph node metastasis, extra-pulmonary metastasis, recurrence and even cause death. Herein, a case of PSP that was huge, presented with multiple lesions and had lymph node as well as extrapulmonary metastases (liver, abdominal cavity, bones) is reported for the first time. This patient was also the first one to die of respiratory and circulatory failure caused by the PSP tumor and its metastases which compressed the mediastinal tissue.